Effects of Sites, Fertilisers and Light on the Growth of Calamus Manan Miquel - Vilayphone, Anoulom (1997)
Calamus manan Miquel is one of the most important rattan species which is being used for furniture manufacturing. Planting of C. manan is being widely promoted to meet the increased demand. The silvicultural requirements of the species have not been well defined. The objective of this study was to evaluate the effects of site, fertilisers and light on the growth of C. manan. The study consisted of three components. The first examined the growth performance on three different sites namely Vlu Seraja, Kota, Vlu Cheka and Serting. The second involved a pot trial examining the effects of chicken dung, POME and NPK (blue) under two light intensities, 100% and 50%. The third was on fertiliser field trials examining the benefit of applying slow release fertilisers and applying fertiliser at an age beyond three years as commonly practised. The results showed that C. manan planted at Uiu Cheka grew better compared to the other sites. The soil at Ulu Cheka was of Typic Paleudult with well drained condition and clay texture. This together with good management in terms of weed control could be the contributory factor in promoting good growth